Micro and Nanobubble Based Strategy for Gas–Liquid–Solid Multiphase Reactions: Palladium-Catalysed Hydrogenation of Carbon–Carbon Unsaturated Bonds - Mase, Nobuyuki; Isomura, Shogo; Toda, Mitsuo; Watanabe, Naoharu (Synlett, 2013)
An autoclave-free, gas–liquid–solid multiphase hydrogenation of carbon–carbon unsaturated bonds using hydrogen micro and nanobubbles (MNBs) is developed. The process allows the liquid phase of the reaction mixture to maintain a high concentration of hydrogen gas.
Keywords: gas–liquid–solid multiphase reactions; hydrogenation; micro and nanobubbles; heterogeneous catalysis; homogeneous catalysis